1998
DOI: 10.1177/1045389x9800900814
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Sensitive Polymeric Actuators

Abstract: This paper reports on the magnetoelastic properties of a recently developed soft and wet material; the magnetic field sensitive polymer gel. It is a polymer network swollen by a ferrofluid. The peculiar magnetoelastic properties may be used to create a wide range of motions and to control the shape change and movement. An understanding of magnetoelastic coupling in gels will hasten the application of gel engineering to switches, sensors, micromachines, biomimetic energy-transducing devices and controlled deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The response time of the samples to the change in magnetic field is less than 60 ms, in agreement with a previous study which reported a response time under 100 ms. [14] The dynamic properties of Magpol in elongation mode were studied using a different electromagnet, deformation of more than 24 000 cycles at 80 Hz can be achieved without a significant shift in strain-field characteristics. In general, it is known that field driven actuators like Magpol have fast switching time and better service life than ionic actuators.…”
Section: Characteristics Of Coiling Actuation Of Magpolmentioning
confidence: 99%
See 4 more Smart Citations
“…The response time of the samples to the change in magnetic field is less than 60 ms, in agreement with a previous study which reported a response time under 100 ms. [14] The dynamic properties of Magpol in elongation mode were studied using a different electromagnet, deformation of more than 24 000 cycles at 80 Hz can be achieved without a significant shift in strain-field characteristics. In general, it is known that field driven actuators like Magpol have fast switching time and better service life than ionic actuators.…”
Section: Characteristics Of Coiling Actuation Of Magpolmentioning
confidence: 99%
“…This type of magneticpolymer composite (Magpol), also termed ferrogel, [1][2][3][4][5][6][7][8] magnetic gels, [9,10] magnetic field sensitive gel, [11][12][13][14][15][16] magnetorheological elastomer, [17,18] or magnetoactive polymer, [19] can readily change its shape and mechanical properties upon exposure to an external magnetic field. Many applications have been identified for Magpol including controllable dampers, [20] stiffness tunable supports, [21] miniature fluid pumps, [22] drug delivery, [23] cancer treatment, [23] sensors, [24,25] soft transducers, and artificial muscles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations